2022
DOI: 10.1002/marc.202200043
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Carbon Nitride‐Based Conjugated Copolymer for Efficient Photocatalytic Degradation of Tetracycline

Abstract: Upcycling waste plastics into advanced semiconductor photocatalysts provides a new strategy to reasonably and economically solve the huge amount of waste plastics, which remains challenging. Herein, a carbon nitride-based donor-acceptor (D-A) conjugated copolymer by copolymerization of dicyandiamide and terephthalic acid from discarded polyethylene terephthalate (PET) using Zn(OH) 2 as catalyst and template at 360-440 °C is synthesized. The morphology and structure of the conjugated copolymer are well regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The broad peaks at 3000–3500 cm –1 are attributable to the amino group (–NH x ) and surface water molecule . The CO stretching vibration of the amide bond and N–H bending vibration are displayed at 1683 and 1543 cm –1 , respectively. The characteristic double peaks of the C–C stretching vibration of the pyridine ring are displayed at 1573 and 1408 cm –1 , and the CN absorption peaks at 1573 and 1408 cm –1 confirm further the presence of the pyridine ring .…”
Section: Resultsmentioning
confidence: 99%
“…The broad peaks at 3000–3500 cm –1 are attributable to the amino group (–NH x ) and surface water molecule . The CO stretching vibration of the amide bond and N–H bending vibration are displayed at 1683 and 1543 cm –1 , respectively. The characteristic double peaks of the C–C stretching vibration of the pyridine ring are displayed at 1573 and 1408 cm –1 , and the CN absorption peaks at 1573 and 1408 cm –1 confirm further the presence of the pyridine ring .…”
Section: Resultsmentioning
confidence: 99%
“…Graphitic carbon nitride(g-C 3 N 4 ), a polymeric compound comprised of carbon, nitrogen, graphene and a minor amount of hydrogen content, has been introduced as a metal-free photo-catalyst that exhibits solar-driven applications [19] and water purification applications [20,21]. The use of this organic semiconductor is advantageous because of its economic feasibility, ease of availability, relatively high stability, and most important intrinsic visible light response [22][23][24][25]. Tian et al reported different dimensional structures of g-C 3 N 4 photo-catalyst.…”
Section: Introductionmentioning
confidence: 99%